Inclusão digital na terceira idade: um estudo de usuários sob a perspectiva fenomenológica - Tatiane Krempser Gandra (2012)
This research is characterized as a study of elderly users to digitally included, whose problematic turns to understanding the phenomenon of transient migration of individuals into the digital age, from the perception of those interviewed. The guiding objective was to understand how the elderly perceive, describe and give meaning to the experience of digital inclusion and its effects on daily life, passing by sociability and the field of information behavior. The option of conducting research with users of old age is justified by the fact that the phenomenon of migration of elderly into the digital age may not exist a few decades from now, because in the future the elderly will have born the in so-called digital age. So, this is an odd time to study issues related to this transient phenomenon. This qualitative study is configured as a descriptive investigation and understanding, based theoretically and methodologically by social phenomenology of Alfred Schutz. The sample consisted of ten seniors, selected from the snowball technique. The survey results show that the elderly go through the process of digital inclusion in rather different ways. For some, this process occurs more naturally, in other words, the elderly naturally incorporate new technologies as soon as they arise, as if there was a break for them, in other words, there is the perception of an exclusion that demands an inclusion. On the other hand, to other seniors, this discontinuity is perceived in different ways, making them feel that they need to find a form of inclusion. We concluded that the perception of the elderly as the phenomenon of digital inclusion that experienced and described in research is strongly influenced by innumerable elements, that we tried to show throughout the data analysis, including: the historicity of the subjects, their individual characteristics, the reasons for inclusion and how they relate to the technology throughout their lives. This last element, the perception of how they relate to technology, is the main factor that influences de behavior of the elderly and permeated all categories of research analysis.